Effects of Repetitive Transcranial Magnetic Stimulation on Cognitive Function in Patients With Stress-Related Depression: A Randomized Double-Blind fMRI and 1H-MRS Study - Chen, Yuxin; Li, Xiuzhen; Wang, Lubin; Tian, Shushi; Chen, Yuanwang; Wang, Feng; Gu, Kesheng; Wang, Ying; Xu, Guangkai; Zhang, Shangrong; Liu, Jie; Wang, Haipeng; et al. (Frontiers in Neurology, 2022)
Objectives: To reveal the effects of repetitive transcranial magnetic stimulation (rTMS) on the improvement of cognitive function in patients with stress-related depression. Methods: We conducted a randomized, double-blind, placebo-controlled study of rTMS in patients with stress-related depression. Patients were randomly allocated to either a sham or experimental group. A 10-session rTMS protocol was used with 10-Hz stimulation over the left DLPFC. Clinical assessments, neuropsychologic, and resting state fMRI and 1H-MRS assessments were executed at two time points—baseline and after the 10th rTMS session. Results: rTMS relieved the mental symptoms of patients in both groups. The MoCA score of patients in the experimental group increased; the number of correct answers increased significantly in Stroop testing, and the number of errors and omissions decreased significantly; the number of persistent errors decreased significantly; and the time used to complete the test decreased to an even greater extent in the WCST experimental group. The ReHo value in the lingual gyrus of the right hemisphere and the cuneus of the left and right hemispheres in the experimental group decreased after treatment. The DC value in the left and right hemispheric cuneus and postcentral gyrus of the left hemisphere in the experimental group diminished after treatment. The functional connections of these brain regions also changed as the Cho and NAA/Cr of the left DLPFC changed, with alterations related to the improvement in cognitive function. The level of choline (Cho) in the left DLPFC of the experimental group was significantly lower than that of the control group, and the level of N-acetylaspartate/creatine (NAA/Cr) in the left DLPFC of the control group was significantly higher than that of the experimental group. These changes were related to the overall improvement in cognitive function. Conclusions: Ten-Hz rTMS over the left DLPFC improved the cognitive function of patients with stress-related depression. The governing mechanism for this phenomenon may be via rTMS effects on multiple visual-related brain regions and their functional connections, and on the somatosensory cortex and its functional connection with visual and auditory cortex—thereby reducing the level of Cho and stabilizing the level of NAA/Cr in the left DLPFC.